أسئلة نشاط فهم المنطوق في منهاج السنة الخامسة ابتدائي دراسة تحليلية تقويمية في ضوء تصنيف بلوم المعرفي - شعيب, رحيمة (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الدراسة إلى تحليل وتقويم أسئلة نشاط فهم المنطوق المضمنة في "دليل استخدام كتاب اللغة العربية للسنة الخامسة ابتدائي" في ضوء تصنيف بن جامين بلوم للمجال المعرفي، والتحقق من المستويات التي استهدفتها هذه الأسئلة، ومدى تنوعها وتحقيقها للأهداف التعليمية المسطرة، و مدى ملاءمتها لخصائص وقدرات المتعلمين والموازنة بين المستويات العليا والدنيا، ومعرفة أكثر أنماط هذه الأسئلة شيوعا واستخداما في هذا الميدان بالتحديد، والوقوف على مدى نجاعة هذه الأسئلة في الرفع من مستوى التحصيل الدراسي للمتعلمين و الارتقاء بهم إلى مستويات عليا في التفكير . Abstract This evaluative and analytical study, with reference to the classification of the Bin Jamin Bloom's cognitive field, aims to verify the levels targeted by the questions relating to the activities of oral comprehension included in the "Guide to the use of the Arabic language manual for the fifth year of primary school. As it checks the extent to which these questions are diversified and well oriented, their suitability for the characteristics and the competence of the learners, and Balance the upper and lower levels and know the most common types of the questions used in this particular area. This study is conducted, as well, to determine the extent of the effectiveness of these questions in raising the level of academic achievement of learners and elevating them to higher levels of thinking.
Article
Keywords: الأسئلة التعليمية، ; فهم المنطوق ; اللغة العربية ; تصنيف بلوم ; السنة الخامسة ابتدائي ; التقويم.; classification ; the fifth year of primary school ; assessment ; Arabic Language